The impact of the audit committee expertise on audit report lag : evidence from Malaysia - Abdulle, Abdinaim Abdi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
This paper investigates the influence of the audit committee expertise on the timeliness of financial information measured by audit report lag. Timeliness of financial information is essential to investors since it impacts their investment decisions. The current study empirically examines the impact of the three audit committee expertise, namely academic accounting, professional accounting, and chief financial officer experience on audit report lag. Audit report lag is defined as the day between the date of financial year-end and the date when the audit report is signed. To achieve a credible study, data were drawn from 91 firms' annual reports among the Malaysian public listed companies for the 2016 financial year-end. Agency theory and resource dependence theory are applied to explain the research framework of the present study. The findings show that the average audit report lag is 95 days, which is lower than the prior studies conducted in Malaysia. This study suggests that there are pieces of evidence of improvement in audit reporting delays among the Malaysian public listed companies.However, contrary to expectations, the multiple regression analysis shows a significant positive relationship between the percentage of the audit committee experts and audit report lag. The findings of the study may be useful to the Malaysian regulatory bodies, such as the Securities Commission and Bursa Malaysia, to better understand the extension of audit works. In addition, the findings could also be useful for a future regulation on the annual filing of reports. This may lead to an improvement in the auditors' time pressure.